Struktur Komunitas Perifiton pada Berbagai Jenis Substrat di Kolam Udang Galah (Makrobrachium rosenbergii de Man) - Putu Darma Utama; Sang Ayu Made Putri Suryani; I Made Kawan (Fakultas Pertanian, Universitas Warmadewa, 2021)
This study aims to determine the species composition, abundance and community structure of periphyton based on biological indices found in various types of substrates in giant prawn ponds (Macrobrachiun rosenbergii de Man). This research was carried out in July-August 2020 in the POKDAKAN Mina Anakan Jepun culture pond, Bebetin Village, Sawan District, Buleleng Regency and identification of periphyton was carried out in the Agricultural Analysis Laboratory, Faculty of Agriculture, Warmadewa University. This study used experimental methods and the data obtained were analyzed descriptively quantitatively. The substrates used are bamboo substrate, palm oil substrate, and PVC pipe substrate with a diameter of 5 x 10 cm2. Periphyton sampling was carried out once every 7 days for 28 days, namely at 07.00-09.00 WITA. The abundance of periphyton on bamboo substrates ranged from 31,338-62,828 ind/cm2, on palm sugar substrates between 33,936–47,083 ind/cm2, and on PVC pipe substrates ranging from 39,592-71,236 ind/cm2. The diversity index value on bamboo substrates ranged from 2.33-3.00, on palm substrates ranged from 2.42-2.80, on PVC pipe substrates ranged from 2.72-2.94. The uniformity index of periphyton on bamboo substrates ranged from 0.72-0.82, on palm oil substrates ranged from 0.70-0.80, and on PVC pipe substrates ranged from 0.81-0.83. The dominance index on bamboo substrates ranged from 0.10-0.19, on palm oil substrates ranged from 0.10-0.21, and on PVC pipe substrates ranged from 0.08-0.10.